Comparison of robotic-assisted and laparoscopic partial nephrectomy based on the PADUA score and the predictive value of the PADUA score and the Mayo Adhesive Probability score for postoperative complications: a single-center retrospective study - Shuo Liu; Bowen Zhang; Bowen Weng; Xiangqiang Liu; Sichuan Hou (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose This study compared perioperative outcomes of robot-assisted partial nephrectomy (RAPN) and laparoscopic partial nephrectomy (LPN) through the PADUA score as well as assessed the predictive value of the PADUA score and the Mayo Adhesive Probability (MAP) score for postoperative complications. Methods Totally 196 patients suffering from RAPN or LPN for renal tumors were reviewed retrospectively. Patients were categorized by PADUA score (low-, moderate-, high-complexity) and MAP score (low-, intermediate-, high-grade). Evaluated outcomes included operative time (OT), warm ischemia time (WIT), estimated blood loss (EBL), drainage duration, postoperative length of stay, and absolute change in estimated glomerular filtration rate (eGFR) at three months post-surgery, along with intra- and postoperative complications. Results RAPN outperformed LPN in the low-complexity group by lowering WIT (P = 0.022) and absolute eGFR change (P = 0.011). For moderate-complexity group, RAPN reduced WIT (P = 0.021), absolute eGFR change (P = 0.027), and postoperative length of stay (P = 0.008). In the high-complexity group, RAPN reduced OT (P = 0.015), WIT (P = 0.023), EBL (P = 0.036), absolute eGFR change (P = 0.024), and postoperative length of stay (P = 0.019). Drainage duration showed no significant differences across groups (P = 0.442, P = 0.327, P = 0.260). RAPN incurred significantly higher total costs than LPN across groups (P < 0.001). ROC analysis suggested PADUA and MAP scores as reliable predictors of postoperative complications in RAPN (AUC = 0.880,0.828) and LPN (AUC = 0.757,0.702). Conclusion RAPN provides significant advantages over LPN in managing complex renal tumors (PADUA score ≥ 10), significantly in reducing OT, WIT, EBL, and absolute eGFR change at three months post-surgery, while minimizing postoperative stay. The PADUA and MAP scores are valuable in predicting postoperative complication. Trial registration number and date of registration Retrospectively registered.